Development of a Novel Electrochemical Immunosensor for Rapid and Sensitive Detection of Sesame Allergens Ses i 4 and Ses i 5 - Huimei Li; Tian’ge Pan; Shudong He; Hanju Sun; Xiaodong Cao; Yongkang Ye (Foods)
Due to their lipophilicity and low content, the major sesame oleosin allergens, Ses i 4 and Ses i 5, are challenging to identify using conventional techniques. Then, a novel unlabeled electrochemical immunosensor was developed to detect the potential allergic activity of sesame oleosins. The voltammetric immunosensor was constructed using a composite of gold nanoparticles (AuNPs), polyethyleneimine (PEI), and multi-walled carbon nanotubes (MWCNTs), which was synthesized in a one-pot process and modified onto a glass carbon electrode to enhance the catalytic current of the oxygen reduction reaction. The oleosin antibody was then directed and immobilized onto the surface of the electrode, which had been modified with streptavidin (SPA), through the fragment crystallizable (Fc) region of the antibody. Under optimized conditions, the immunosensor exhibited a linear response within a detection range of 50 to 800 ng/L, with detection limits of 0.616 ng/L for Ses i 4 and 0.307 ng/L for Ses i 5, respectively. The immunosensor demonstrated excellent selectivity and stability, making it suitable for the quantification of sesame oleosins. The comparative analysis of various detection methods for sesame allergens was conducted, revealing that the immunosensor achieved a wide detection range and low limit of detection (LOD). Compared to traditional enzyme-linked immunosorbent assay (ELISA), the immunosensor successfully quantified the allergenicity potential of Ses i 4 and Ses i 5 in roasted sesame seeds at temperatures of 120 °C, 150 °C, and 180 °C. This innovative method offers a new perspective for the rapid quantification of sesame oleosins in foods and real-time monitoring of allergic potential, providing significant advancements in the field of food allergy detection.